1995
DOI: 10.1021/bi00020a004
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structures of matrilysin-inhibitor complexes

Abstract: Matrix metalloproteases are a family of enzymes that play critical roles in the physiological and pathological degradation of the extracellular matrix. These enzymes may be important therapeutic targets for the treatment of various diseases where tissue degradation is part of the pathology, such as cancer and arthritis. Matrilysin is the smallest member of this family of enzymes, all of which require zinc for catalytic activity. The first X-ray crystal structures of human matrilysin are presented. Inhibitors o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
150
1
4

Year Published

1997
1997
2009
2009

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 255 publications
(157 citation statements)
references
References 44 publications
2
150
1
4
Order By: Relevance
“…However, the hydroxamate derivative of oleic acid did not significantly improve its inhibitory capacity (24), whereas 200-and 500-fold enhancements in inhibitory capacity from carboxylate to hydroxamate inhibitors were previously reported for matrilysin and collagenase-1, respectively (33,34); in addition, the alcohol analogue of oleic acid, a compound unable to chelate the catalytic zinc, was also found nearly as effective as oleic acid in inhibiting gelatinase A, suggesting that, at least for gelatinases, zinc chelation was not the main determinant in enzyme inhibition by fatty acids.…”
Section: Effect Of Elaidic Acid On the Degradation Of Human Skin Collcontrasting
confidence: 54%
“…However, the hydroxamate derivative of oleic acid did not significantly improve its inhibitory capacity (24), whereas 200-and 500-fold enhancements in inhibitory capacity from carboxylate to hydroxamate inhibitors were previously reported for matrilysin and collagenase-1, respectively (33,34); in addition, the alcohol analogue of oleic acid, a compound unable to chelate the catalytic zinc, was also found nearly as effective as oleic acid in inhibiting gelatinase A, suggesting that, at least for gelatinases, zinc chelation was not the main determinant in enzyme inhibition by fatty acids.…”
Section: Effect Of Elaidic Acid On the Degradation Of Human Skin Collcontrasting
confidence: 54%
“…These peptides were chosen based on knowledge gained from structure-function studies performed on other MMPs. The structures for the catalytic domains of several members of the MMP family have recently become available including human fibroblast collagenase (MMP-1) (22-24), human stromelysin-1 (MMP-3) (25,26), human matrilysin (MMP-7) (27), and human neutrophil collagenase (MMP-8) (28 -30). These structures revealed that the SЈ 1 subsite is the most well defined pocket in these MMPs and consists of a hydrophobic pocket which varies greatly in its depth.…”
Section: Figmentioning
confidence: 99%
“…These structures revealed that the SЈ 1 subsite is the most well defined pocket in these MMPs and consists of a hydrophobic pocket which varies greatly in its depth. Mutational analyses of the SЈ 1 pocket (29) revealed that residue 214 (numbering according to Browner (27)) which lies at the bottom of the SЈ 1 pocket is critical in determining its shape. For MMP-1 and MMP-7, which have an Arg 214 and a Tyr 214 , respectively, these residues point into the SЈ 1 pocket, thus forming a shallow pocket.…”
Section: Figmentioning
confidence: 99%
“…ics, hydroxamic acid derivatives (2,14,21,22), phosphinamides and sulfodiimines (23,24), thiadiazole (25), and malonic acid derivatives (26,27).…”
mentioning
confidence: 99%